First descriptions of the final stadium larva of Heliogomphus chaoi Karube, 2004 and the adult female of Microgomphus jurzitzai Karube, 2000 from Vietnam (Odonata: Gomphidae) - Phan, Quoc Toan; Keetapithchayakul, Tosaphol Saetung (Zootaxa, 2023)
The larva of Heliogomphus chaoi Karube, 2004 and the adult female of Microgomphus jurzitzai Karube, 2000 are described from Vietnam for the first time. The morphological difference between the larvae of the genera Heliogomphus Laidlaw, 1922 and Microgomphus Selys, 1858 are discussed, which throws doubts about the current taxonomic status of H. retroflexus (Ris, 1912).